2009
DOI: 10.1111/j.1471-4159.2009.06109.x
|View full text |Cite
|
Sign up to set email alerts
|

The brain selenoproteome: priorities in the hierarchy and different levels of selenium homeostasis in the brain of selenium‐deficient rats

Abstract: The application of radionuclides for the localization of essential trace elements in vivo and the characterization of their binding proteins is a story of intermittently made improvements of the techniques used for their detection. In this study we present the use of neutron activation analysis and different autoradiographic imaging methods including real‐time digital autoradiography to reveal new insights in the hierarchy of selenium homeostasis. Selenoproteins containing the essential trace element selenium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 59 publications
3
44
0
1
Order By: Relevance
“…Imaging using a 75 Se radiotracer combined with autoradiographic localisation and proteomic analysis to profile Se levels in different brain regions of rats fed a Se-replete diet revealed that Se was enriched in choroid plexus, putamen, parietal inferior lobule and occipital cortex. 35 This observation has been reflected in human brains, where the highest Se concentration occurs in grey matter, with the putamen, parietal inferior lobule and occipital cortex in particular, while the lowest levels are found in the cerebellum and medulla. 36 The mechanism that maintains Se levels in the brain at the expense of other organs, even during times of deprivation, is mainly orchestrated by SelP, which is recognised as the most important Se supply to different tissue types.…”
Section: Selenoprotein P and Brain Selenium Hierarchymentioning
confidence: 92%
See 2 more Smart Citations
“…Imaging using a 75 Se radiotracer combined with autoradiographic localisation and proteomic analysis to profile Se levels in different brain regions of rats fed a Se-replete diet revealed that Se was enriched in choroid plexus, putamen, parietal inferior lobule and occipital cortex. 35 This observation has been reflected in human brains, where the highest Se concentration occurs in grey matter, with the putamen, parietal inferior lobule and occipital cortex in particular, while the lowest levels are found in the cerebellum and medulla. 36 The mechanism that maintains Se levels in the brain at the expense of other organs, even during times of deprivation, is mainly orchestrated by SelP, which is recognised as the most important Se supply to different tissue types.…”
Section: Selenoprotein P and Brain Selenium Hierarchymentioning
confidence: 92%
“…2 (a) SelP, the master protein driving Se bioavailability is synthesised in the liver from both inorganic and organoselenium compounds accessible through dietary sources. At the blood-brain barrier, SelP releases Se into the CNS via the ApoER2 receptor, which is in turn incorporated into newlyformed SelP in astrocytes (figure adapted from Burk et al 35 ), or is transported directly to neurons (dashed arrow). SelP is made available to neurons via the same membrane-bound ApoER2, where additional selenoproteins essential to neurological function (blue box) are biosynthesised.…”
Section: Selenoprotein P and Brain Selenium Hierarchymentioning
confidence: 98%
See 1 more Smart Citation
“…That underlines a high priority for Se uptake and retention in the CSF during marginal dietary Se supplementation. CSF was identified before as a key part of the brain Se homeostasis showing the highest uptake of the applied 75 Se in the brain, suggesting a high turnover rate of Se in the ventricular system [11].…”
Section: Se and Se Species In Csfmentioning
confidence: 99%
“…The authors assumed that the Se uptake is regulated by a brain region-specific expressed receptor and that the expression of the receptor is nutritionally regulated by the Se status. Within the CNS, CSF showed the highest uptake of the applied 75 Se (intraperitoneal injection) and the authors suggested a high turnover rate of this Se in the ventricular system [11].…”
Section: Introductionmentioning
confidence: 98%